2007
DOI: 10.1111/j.1365-246x.2007.03445.x
|View full text |Cite
|
Sign up to set email alerts
|

Source mechanism of the 2000 November 15 Lake Van earthquake (Mw= 5.6) in eastern Turkey and its seismotectonic implications

Abstract: SUMMARY Detailed source process of the 2000 November 15 Lake Van (eastern Turkey) earthquake (Mw= 5.6) was retrieved using the method of Kikuchi & Kanamori for source inversion of complex body waveforms. The event has been reported by USGS as a deep (67 km) subcrustal earthquake resulting from a rupture on a normal fault beneath the Bitlis Suture zone where continental collision is in action between the Arabian and Eurasian plates. However, our source model based on the analysis of complex body‐waveforms sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 42 publications
0
22
0
1
Order By: Relevance
“…Optimum yönlenmiş fay üzerinde gerilme değişim hesapları öncelikle asal gerilme eksenleri yönelimleri ile bölgesel gerilme alanının tanımlanmasını gerektirir. Buna göre, bu çalışmada [16] tarafından verilen bölgesel gerilme alanı (σ1 için, azimuth=335…”
Section: Coulomb Geri̇lme Deği̇şi̇mi̇ Modeli̇ Ve Sonuçlar (Coulomb Stress unclassified
“…Optimum yönlenmiş fay üzerinde gerilme değişim hesapları öncelikle asal gerilme eksenleri yönelimleri ile bölgesel gerilme alanının tanımlanmasını gerektirir. Buna göre, bu çalışmada [16] tarafından verilen bölgesel gerilme alanı (σ1 için, azimuth=335…”
Section: Coulomb Geri̇lme Deği̇şi̇mi̇ Modeli̇ Ve Sonuçlar (Coulomb Stress unclassified
“…When the principal stress axis, σ 3 , is vertical and Σ2 is horizontal, stress field is defined by a reverse faulting type (Twiss & Moores, 1992). More detailed information about R (shape factor) is given by Bellier and Zoback (1995) and Pınar et al (2007). The regional stress tensor analysis for the shape and orientation of the stress tensor calculated from 30 fault plane (totally 30; 7 earthquakes since 1672 plus the 8 January 2013 earthquake and its 22 aftershocks) solutions (Figure 7(a) and (b)).…”
Section: Moment Tensor Solution and Stress Tensor Analysismentioning
confidence: 99%
“…Local tectonic features, epicentral distribution of large earthquakes (red and green stars) and available focal mechanisms (blackwhite beach balls) for the Lake Van area along with the bathymetry of Lake Van. Extent of faults are from Wong and Finckh (1978), Koçyigit et al (2011) andMTA (2012), focal mechanisms are from McKenzie (1972), Pınar (1995), Pınar et al (2007), Utkucu (2013a) and USGS-NEIC and the bathymetry of Lake Van is from Wong and Degens (1978). See Table 2 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The earthquake focal mechanisms of the recent earthquakes in the area have indicated that the type of faulting along the boundary faults is mainly thrusting (Fig. 2) (Pınar et al, 2007;Utkucu, 2013a). Pınar et al (2007) performed a stress tensor inversion of the available focal mechanisms and found that the stress regime was transpressive with a maximum compression axis roughly in the N-S direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation